LINC00853 contributes to tumor stemness of gastric cancer through FOXP3-mediated transcription of PDZK1IP1 - Xia Hu; Maoyuan Zhao; Shuangyuan Hu; Qingsong Liu; Wenhao Liao; Lina Wan; Feng Wei; Fangting Su; Yu Guo; Jinhao Zeng (Biological Procedures Online, 2023)
Abstract Background The incidence and mortality of gastric cancer (GC) are high worldwide. Tumor stemness is a major contributor to tumorigenesis and development of GC, in which long non-coding RNAs (lncRNAs) are deeply involved. The purpose of this study was to investigate the influences and mechanisms of LINC00853 in the progression and stemness of GC. Methods The level of LINC00853 was assessed based on The Cancer Genome Atlas (TCGA) database and GC cell lines by RT-PCR and in situ hybridization. An evaluation of biological functions of LINC00853 including cell proliferation, migration, and tumor stemness was conducted via gain-and loss-of-function experiments. Furthermore, RNA pull-down and RNA immunoprecipitation (RIP) assay were utilized to validate the connection between LINC00853 and the transcription factor Forkhead Box P3 (FOXP3). Nude mouse xenograft model was used to identify the impacts of LINC00853 on tumor development. Results We identified the up-regulated levels of lncRNA-LINC00853 in GC, and its overexpression correlates with poor prognosis in GC patients. Further study indicated that LINC00853 promoted cell proliferation, migration and cancer stemness while suppressed cell apoptosis. Mechanistically, LINC00853 directly bind to FOXP3 and promoted FOXP3-mediated transcription of PDZK1 interacting protein 1(PDZK1IP1). Alterations of FOXP3 or PDZK1IP1 reversed the LINC00853-induced biological effects on cell proliferation, migration and stemness. Moreover, xenograft tumor assay was used to investigate the function of LINC00853 in vivo. Conclusions Taken together, these findings revealed the tumor-promoting activity of LINC00853 in GC, expanding our understanding of lncRNAs regulation on GC pathogenesis.